2019
DOI: 10.1097/mjt.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Outcomes of Patients With Heart Failure Undergoing Catheter Ablation of Atrial Fibrillation

Abstract: Background: Catheter ablation is being increasingly performed for rhythm control of atrial fibrillation (AF). Heart failure (HF) frequently coexists with AF because they share common risk factors. Study Question: This study aims at identifying the characteristics and procedural outcomes of patients with HF undergoing catheter ablation of AF. Study Design: In this retrospective cohort study, we analyzed 264 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…It has been reported that the procedure and fluoroscopic time in patients with HF are significantly longer than those without HF. Substrate remodeling and enlargement of LA may be some of the important reasons 17,28 . However, our analysis identified similar procedure and fluoroscopic time periods for patients with HFpEF compared with those without HF, which was in agreement with previous studies 17,18 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It has been reported that the procedure and fluoroscopic time in patients with HF are significantly longer than those without HF. Substrate remodeling and enlargement of LA may be some of the important reasons 17,28 . However, our analysis identified similar procedure and fluoroscopic time periods for patients with HFpEF compared with those without HF, which was in agreement with previous studies 17,18 .…”
Section: Discussionsupporting
confidence: 91%
“…Substrate remodeling and enlargement of LA may be some of the important reasons. 17,28 However, our analysis identified similar procedure and fluoroscopic time periods for patients with HFpEF compared with those without HF, which was in agreement with previous studies. 17,18 The reasons may be as follows: The aforementioned factors may contribute to the nonsignificant differences in the procedure and fluoroscopic time observed for patients with HFpEF and without HF.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A total of 5 studies were included in this review after screening and reviewing potentially relevant studies in detail ( Fig. 1 ) [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the incidence of heart failure has been increasing year by year. It is approximately 1.5% among adults, and that in the elderly people over 70 years old is even exceeding 11% [15]. Studies have proved that patients with atrial fibrillation are often accompanied by different degrees of heart failure.…”
Section: Discussionmentioning
confidence: 99%